Nonconscious Control of Voice Intensity During Vocalization - HAFKE, Honorata (Archives of Acoustics, 2009)
There are two separate visual systems in the human brain. Evidence from studies on both the humans and other primates has shown that there is a distinction between vision for perception and vision for action, which is reflected in the organization of the visual pathways in the cerebral cortex of primates. In recent years, researchers have attempted to find a similar dissociation between action and perception in human audition. The hypothesis tested in this paper is that the voice intensity is tracked and controlled by an auditory motor system. The results of this control are used for nonconciously correct the vocal production. To observe the dissociation between perception and motor control, a subliminal experimental situation was created, in which values below the perceptual threshold (values which were not processed through normal channels or apparatus of perception) were used. The hypothesis was that a subliminal modification of an auditory voice feedback would cause an appropriate correction as a response, even if this change was not actually perceived. Assuming that the auditory system functions in the same way as the visual one and processes the information vital for motor reactions in real time, a reaction that would compensate such a modification should be expected.